Reading Comprehension as an Absolute Necessity in Teaching Arabic for Non-Native Learners - Muhammad Sabri bin Sahrir (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
AbstractLearners of Arabic as a second language may have difficulty in reading comprehension. This article will not provide any radical solutions with regards to the issue, but it will contribute to the development of its understanding and analysis skills. Taking this student's hand step by step without introducing it in details is a way of understanding the reading of the students of Arabic as a second language. Therefore, this student is in dire need of presenting the reading comprehension with a different perspective. We need to change the style of presentation to non-Arabic speakers; it has the first language aspects that speak and the degree of proximity to the Arabic language or away from them. The Arab schools of non-people need the latest scientific findings of the world in the teaching of reading comprehension in any language. The comprehensive in all languages taught through texts that understand the meaning of depth and aware of the dimensions. Also, to know what is meant by and then derive from them what we want from the rules, vocabularies, and information. So that we can live texts of the reality that the student lives in his study and can use the structure to agree with the community after that. Perhaps this agrees with what has been settled by the reading comprehension in modern linguistic theories. So, this study focuses on a special class of students who represent the Arabic language with the second language.Keywords: reading comprehension, Arabic as a second language, reading, reading comprehension, learning difficulty. الفهم القرائي ضرورة حتمية في تدريس اللغة العربية للناطقين بغيرها محمد صبر بن سهريرالجامعة العاليمة الإسلامية مالزياmuhdsabri@iium.edu.my ملخصإن متلقي اللغة العربية بوصفها لغة ثانية قد يواجه صعوبات في الفهم القرائي للغة العربية. ويجب أن ينظر في هذه المادة على أنها لن تقدم لدارس حلولا جذرية ولكنها ستسهم في تطوير مهاراته في مجالات الفهم والتحليل. فالأخذ بيد هذا الطالب خطوة خطوة دون إدخاله في تفاصيل هي بمثابة رسم طريق للفهم القرائي للطلاب الدارسين للغة العربية بوصفها لغة ثانية؛ لذلك، هذا الطالب بحاجة ماسة لتقديم الفهم القرائي بمنظور مختلف، فإذا كانت الدراسات السابقة قد سارت من قبل وإلى الآن على تقديم الفهم القرائي لدارسينا العرب أو من لغتهم الأولى العربية في صورة نصوص جافة منقطعة عن الواقع، مفصولة عن التفكير مما جعلهم ينفرون عن هذه الدراسة وكفانا ما تلقاه "زيد من ضرب عمرو" فإننا بحاجة لتغيير نمط تقديمها للناطقين بغير العربية، فعنده أوجه اللغة الأولى التي يتكلمها ودرجة قربها من اللغة العربية أو ابتعادها عنها.ودارس العربية من غير أهلها يحتاج لأحدث ما توصل إليه العالم من نظريات علمية تمارس في تدريس الفهم القرائي في أي لغة، والفهم القرائي بمعناه الشامل في كل اللغات صار يدرس من خلال نصوص يفهم معناها بعمق، وتدرك أبعادها والمقصود منها ثم يستنبط منها ما نشاء من قواعد ومفردات ومعلومات، ونصوص حية من الواقع الذي يعيشه الطالب في دراسته ويستطيع استخدام التركيب بما يوافق مجتمعه بعد ذلك، ولعل هذا يوافق ما استقر عليه الفهم القرائي في النظريات اللغوية الحديثة. إذن فهذه الدراسة تركز على فئة خاصة من الطلبة تمثل اللغة العربية لديهم اللغة الثانية.كلمات مفتاحية: الفهم القرائي، اللغة العربية بوصفها لغة ثانية، القراءة، الفهم القرائي، صعوبة التعلم